Passenger Seat Design and Analysis for Railway Executive Transportation - Zainuddin; Anggara, Aditya; Setiawan, Dibyo; Setiawan, Apri (Jurnal Konversi Energi dan Manufaktur, 2025)
The design of executive chairs for trains was carried out to improve safety, comfort and aesthetics of the train. Seat design innovation was made by prioritizing passenger comfort and paying attention to the S curve of the passenger's spine. This research carried out a redesign of the Indonesian railway executive chair with the added advantage of a chair that can be tilted up to 40° from the initial position of 10°. After the design concept is selected, a simulation will be done on three critical parts of the train seat including chair frame, footrest, and footrest frame. According to investigation, there are facilities tailored to user needs, starting from a folding table, middle arm rest, reclining seat 40°, rotate system 180°, and footrest. The mechanism used for reclining seats with the help of a gas spring to adjust the backrest and a rotate system mechanism with plate bearings. Thus, the seat can be adjusted to the direction of the train's advance. The final chair dimensions of 1101x´1091´x632 mm and material ASTM A36, polypropylene, rubber.